Hollowed out : why the economy doesn't work without a strong middle class - Madland, David (University of California Press, 2015)
"For the past several decades, politicians and economists have thought that high levels of inequality were good for the economy. But an economy that works only for the rich simply doesn't work. Because the middle class is so weak, America's economy now suffers from the kinds of problems that plague less-developed countries. Privileged elites more frequently secure special treatment from a government that wastes money and stifles competition. Children's opportunities are excessively determined by the wealth of their parents. Societal distrust has increased, making business transactions needlessly difficult. Consumer demand has weakened and become unstable, which has helped fuel the Great Recession and has made the recovery painfully slow. As Hollowed Out explains, to have strong and sustainable growth, the economy needs to work for everyone and grow from the middle out. This new middle-out theory aims to supplant trickle-down economics--the theory that was so wrong about inequality and our economy and did so much damage to our nation. This new thinking has the potential to shape economic policymaking for generations."--Provided by publisher